TINJAUAN PRODUKTIVITAS PEKERJA PADA DUA PROYEK SERTA FAKTOR YANG MEMPENGARUHINYA - Fuk Jin Oei; Sudarno P Tampubolon; Chatarina Finella (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2023)
Labor productivity is one of the critical success factors in a development project of construction services. This research to analyze the worker’s productivity on two projects undertaken by two contractors with different background. Labor Utilization Rate Value (LUR Value) is used in this study to determine the level of productivity of each worker. Meanwhile, to determine the factors which affect the labor’s productivity, factor analysis is used in this study supported the spread of questionnaire to the supervisors. It can be seen that the average level of worker productivity on rebar work in project A which has been undertaken by one of the foreign contractor was 71,4881% and LUR value for formwork workwas 74,3086%, while the project B which has been done by one of the BUMN contactors, LUR value on rebar work was 66,1528 % and on the formwork work was 72,5055 %. Of the same type of work, LUR value comparison shows that productivity of workers on the project A is higher. Meanwhile, factor analysis on the questionnaire shows that some factors which affect on project A are work method, work instructions, tools quality, group labor composition, working drawings, remunerations, area density of labor, labor skills, experience and teamwork. While, factors that affect labor productivity on the project B are expertise of labor, area density of labor, experience, group labor composition, work method, management and leadership skill, team work and tools quality. Keywords: productivity, labor utilization rate, productivity factor, labor, factor analysis